Administrative Service Standards at the Department of Population and Civil Registration (DISDUKCAPIL) Deli Serdang - Elma Fadilah; Andri Soemitra (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
One of the public services organized by the government is administrative services. Administrative services are services that produce various forms of official documents needed by the community. The purpose of this study was to see how the standard of administrative services in the office of population and civil registration (DISDUKCAPIL) is. The research method used in this research is using qualitative methods. Where the results of the study show that the standard of administrative services carried out by the Office of Population and Civil Registration (Disdukcapil) Deli Serdang is considered to be quite good. Although there are some things that need to be improved again in the future such as existing facilities and infrastructure..